2015
DOI: 10.1002/ange.201505462
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Degradation of Sulfur Hexafluoride by Rhodium Complexes

Abstract: The development of asafe and efficient method for the degradation of SF 6 is of current environmental interest, because SF 6 is one of the most potent greenhouse gases.SF 6 is thermally and chemically extremely inert, and therefore,ithas been used in various industrial applications.H owever,t his inertness results in am ajor challenge for its depletion. We report on ap rocess for ac atalytic degradation of SF 6 in the homogeneous phase by using rhodium complexes as precatalysts.T he SF 6 activation reactions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…F -), respectively. Although the elemental electrochemical steps of SF 6 reduction are not currently known, SF 6 has been reported to decompose by rapid fluoride ion rejection [29] and our previous study of the perfluorinated gas analogue, NF 3 , showed electron-coupled fluoride expulsion to be the likely conversion mechanism. [10b] Thus, it is probable that "lone" metastable Fmay be generated during discharge, with finite lifetimes in the electrolyte before complexation with Li + and subsequent precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…F -), respectively. Although the elemental electrochemical steps of SF 6 reduction are not currently known, SF 6 has been reported to decompose by rapid fluoride ion rejection [29] and our previous study of the perfluorinated gas analogue, NF 3 , showed electron-coupled fluoride expulsion to be the likely conversion mechanism. [10b] Thus, it is probable that "lone" metastable Fmay be generated during discharge, with finite lifetimes in the electrolyte before complexation with Li + and subsequent precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…4c) is consistent with the shift of the Li/Li + redox potential between glyme (DME) and DMSO, and may not reflect significant change in the SF6 reduction potential. 147 The fact that the Li + solvation strength may alter the attainable cell voltages indicates that Li + is likely not concertedly transferred in the cathode reduction reaction, but rather chemically precipitates the ejected F -(SF6 is known to decompose in the gas phase through anion ejection upon spark discharge activation), 148 such that it factors in the anode potential and does not cancel out in the cathode potential. The precise multi-step reduction mechanisms remain unclear as the highly complex branching over multiple electron-transfer steps evades experimental measurement to date.…”
Section: 'Beyond O2' Gas Cathodesmentioning
confidence: 99%
“…4d). It will be of interest to determine whether catalysts, which have been shown to activate SF6 in homogeneous contexts, 150,151 may be able to address the high overpotential issues.…”
Section: 'Beyond O2' Gas Cathodesmentioning
confidence: 99%
“…Traditional SF 6 degradation technologies including thermal degradation, thermal catalytic degradation, photodegradation, and so forth have disadvantages such as high energy consumption, low degradation efficiency, and long degradation time, which limit their large-scale industrial applications. [3][4][5][6][7][8] Among the current SF 6 degradation methods, nonthermal plasma (NTP) is considered to be one of the most efficient methods, because NTP can produce abundant energetic reactive species to decompose contaminants in a very short time. In the previous work, researchers primarily focused on studying the SF 6 degradation properties by different discharge types, including radio frequency (RF) discharge, microwave discharge, corona discharge, and dielectric barrier discharge (DBD).…”
mentioning
confidence: 99%
“…The mean electron energy and rate coefficient for SF 6 excitation in SF 6 /Ar system are significantly higher than those in SF 6 /N 2 or SF 6 /air system, which results in higher SF 6 degradation efficiency in SF 6 /Ar system. Moreover, the response surface methodology based on the Box-Behnken design model was constructed to optimize several key process parameters including pulsed voltage, gas flow rate, oxygen content, and relative humidity, as well as assess the contribution of each parameter to SF 6 Sulfur hexafluoride (SF 6 ) is widely used as an insulating gas in the power industry because of its excellent electrical insulation and arc extinguishing properties. [1] However, it is listed as a greenhouse gas because of its high global warming potential value of 23 900.…”
mentioning
confidence: 99%